UTILIZATION OF IN-Situ WASTE FROM COFFEE PLANT (Coffea sp.) AS MULCH AGAINST DROUGHT RESISTANCE OF SIGARARUTANG VARIETY ARABIC COFFEE SEEDLINGS - Rusmindo Leny Natalina Hutagalung; Nurhayati; Yayuk Purwaningrum (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
This research was carried out at the experimental field of the Faculty of Agriculture, Islamic University of North Sumatra, Jln. Karya Wisata, Medan Johor District, Medan City, North Sumatra Province. The altitude is ± 25 meters above sea level, with flat topography with soil types of the inceptisol order. This research aims to determine the in situ waste of coffee plants (coffea sp.) as mulch on the drought resistance of Arabica coffee seedlings of the Sigararutang variety. This research consisted of II research stages, namely stage I using a Factorial Split Plot Design (RPT) which consisted of 2 treatment factors, namely: various types of coffee roots (A) and watering intervals (P). The first factor A1 = Fishing roots, A2 = Needle roots and the second factor P1 = Every day watered, P2 = Once every two days watered. The parameters observed were plant height (cm), number of leaves (strands), root length (cm), Wet weight (g) and dry weight (g) and for the second phase of research using a factorial completely randomized design (RAK) consisting of 2 treatment factors, namely: P1=watered every day, P2=watered every two days, P3=three days once watered, the parameters observed were plant height (cm), number of leaves (strands), root length (cm), root volume (ml), root dry weight (g), shoot dry weight (g) and shoot root ratio (NTA). ). The results of phase I research showed that providing watering intervals had a significant effect on drought resistance in coffee seedlings for all observed variables, namely fresh weight, wet weight and coffee stomata. The results of the research showed that providing various types of roots had a significant effect on drought resistance in coffee seedlings for all observed variables, namely coffee stomata. There was no interaction between providing watering intervals and various types of coffee roots. The results of phase II research showed that providing watering intervals had a significant effect on drought resistance in coffee seedlings for all observed variables, namely root dry weight 2 and 3 WST, shoot dry weight 1 and 2 WST, shoot root ratio 1 WST and coffee stomata. The results of the research showed that The provision of various types of roots has a significant effect on the drought resistance of coffee seedlings, all observation variables, namely root dry weight 1 and 2 BST and coffee stomata. There is an interaction between the provision of watering intervals and various types of coffee roots, all observation variables, namely root dry weight 2 WST.